1991
DOI: 10.1086/116030
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction limited infrared images of the binary star T Tauri

Abstract: High-resolution images of T Tau and its infrared companion have been reconstructed from near-and mid-infrared data collected at the Hale 5 m telescope. The near-infrared (1-5 fim) results were obtained by two dimensional speckle imaging and the mid-infrared (10-20 ¡im) results were derived from shift and add procedures applied to slit scans. The spectral energy distributions of the separated components were constructed from 1 to 20 [im data collected in less than half a year (1990 September to 1991 January). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 21 publications
15
133
0
Order By: Relevance
“…This requires one to assume that the IR flux ratio within the T Tau S system remains constant. Evidence for large variability in at least one of the two components of the system is growing, however (Ghez et al 1991;Beck et al 2004).…”
Section: Fitting Methodsmentioning
confidence: 99%
“…This requires one to assume that the IR flux ratio within the T Tau S system remains constant. Evidence for large variability in at least one of the two components of the system is growing, however (Ghez et al 1991;Beck et al 2004).…”
Section: Fitting Methodsmentioning
confidence: 99%
“…High-resolution near-infrared observations ( Dyck et al 1982) revealed early that it had a companion (hereafter T Tau S) located 0.7 00 to its south, whose nature remains somewhat mysterious. T Tau S has about twice the bolometric luminosity of the optical star T Tau (which we will refer to as T Tau N in the rest of the paper) and is very significantly more obscured (e.g., Koresko et al 1997;Stapelfeldt et al 1998); indeed, its spectral energy distribution peaks around 3 m (Ghez et al 1991). The relative motion between T Tau N and T Tau S (Ghez et al 1991;Roddier et al 2000;Duchêne et al 2002Duchêne et al , 2005) strongly suggests that they are physically bound to each other.…”
Section: Optical and Infrared Observationsmentioning
confidence: 97%
“…T Tau S has about twice the bolometric luminosity of the optical star T Tau (which we will refer to as T Tau N in the rest of the paper) and is very significantly more obscured (e.g., Koresko et al 1997;Stapelfeldt et al 1998); indeed, its spectral energy distribution peaks around 3 m (Ghez et al 1991). The relative motion between T Tau N and T Tau S (Ghez et al 1991;Roddier et al 2000;Duchêne et al 2002Duchêne et al , 2005) strongly suggests that they are physically bound to each other. In addition, the comparison between the transverse ($5 km s À1 ; Beck et al 2004) and radial ($2.5 km s À1 ; Duchêne et al 2005) components of the relative orbital motion shows that the orbit is close to being in the plane of the sky (i 30 ) and is, therefore, very likely to be roughly coplanar with the circumstellar disk surrounding T Tau N.…”
Section: Optical and Infrared Observationsmentioning
confidence: 97%
“…The northern optical source (hereafter T Tau N) was found to have an infrared companion, T Tau S, approximately 0.7 to the south (Dyck et al 1982;Ghez et al 1991). T Tau S has been found also to be binary, with a separation of approximately 100 mas (Koresko 2000;Köhler et al 2000).…”
Section: Introductionmentioning
confidence: 99%